Lumbosacral plexus injury following vaginal delivery with epidural analgesia -A case report - Park, Seil; Park, Sung Wook; Kim, Keon Sik (Korean journal of anesthesiology, 2013)
A 26 year old, healthy, 41 week primiparous woman received a patient-controlled epidural analgesia (PCEA) and experienced paraplegia 11 hours later after a vaginal delivery. This was thought to be the result of complications from PCEA but there was no specific abnormality on magnetic resonance imaging (MRI) of the lumbosacral spine. On an electromyography (EMG) study performed 15 days following delivery, signs of tibial neuropathy were present and peripheral nerve injury during vaginal delivery was suspected. Motor weakness and hypoesthesia of both lower extremities improved rapidly, but a decrease in the desire to urinate or defecate, followed by urinary incontinence and constipation persisted, We suspected the sacral plexus had been severely damaged during vaginal delivery. Seven months later, the patient's conditions improved but had not fully recovered.